Pengaruh Kepemimpinan Birokrasi dan Kompetensi terhadap Kinerja Pegawai - Ngabito, Dewi; Pakaya, Idan I. (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Leadership is a way for leaders to direct, encourage, and organize elements of a group or organization to achieve the desired goals, thereby improving employee performance to the maximum. This study aims to find out and analyze the influence of Bureaucratic leadership and competence on the performance of Employees at the North Gorontalo Regency Transmigration and Manpower Office. This study uses a quantitative method. The population as well as a sample of this study is all employees of the North Gorontalo Regency Transmigration and Manpower Office. Data analysis uses multiple regression. The results of the study show that bureaucratic leadership and competence affect the performance of employees at the North Gorontalo Regency Transmigration and Manpower Office both partially and simultaneously.